Literature Riview Understanding Interests and Talents in Improving High School Students' Learning Motivation - Aida Safitri; Graciella Lumban Gaol; Aziz Andreansyah; Alrefi, Alrefi (Journal of Insan Mulia Education, 2025)
Many high school students still do not understand what their interests and talents are, so this has an impact on low learning motivation and lack of enthusiasm in following the learning process. In fact, learning motivation is one of the important factors that determine the success of education, and understanding interests and talents can be the key to increasing students' enthusiasm and learning achievement. This study aims to examine the relationship between interests and talents and learning motivation through a literature review approach to 20 relevant scientific journal articles. Previous research is used as the main source in examining the phenomenon being discussed, so that a more comprehensive and in-depth understanding can be obtained. The results of the analysis show that students who recognize their potential tend to be more active, enthusiastic, and achieve better learning outcomes, while lack of attention to individual potential can actually reduce learning enthusiasm. From these findings, it can be concluded that the role of teachers, schools, and families is very important in helping students recognize and develop their interests and talents. With the right support, students' learning motivation can be improved sustainably. The results of this study are expected to be practical input for educators and parents in designing a more personal learning approach that is in accordance with the potential of each student.